Antioxidant, Cytotoxic and Antimicrobial Activity of Chitosan Preparations Extracted from Ganoderma Lucidum Mushroom. Issue 7 (5th June 2020) - Savin, Simona; Craciunescu, Oana; Oancea, Anca; Ilie, Daniela; Ciucan, Teodora; Antohi, Loredana Stefania; Toma, Agnes; Nicolescu, Alina; Deleanu, Calin; Oancea, Florin
Abstract: Two chitosan extracts were prepared by chemical and enzymatic treatment of Ganoderma lucidum mushroom, as an alternative source to crustacean shells. The molecular weight of the enzymatic extract was lower than that of the chemical one and of shrimp chitosan, as determined by viscosity measurements. Characteristic signals were identified in the 1 H‐NMR spectra and high deacetylation degree indicated good physico‐chemical properties for both mushroom chitosan extracts. The scavenging capacity of mushroom chitosan extracts was moderate against the synthetic radicals of 2, 2′‐azinobis(3‐ethylbenzothiazoline‐6‐sulfonic acid) (ABTS) and 1, 1‐diphenyl‐2‐picrylhydrazyl (DPPH), but higher values were observed for the enzymatic extract, compared to the chemical extract and shrimp chitosan. In vitro cytotoxicity was evaluated in L929 mouse fibroblast cell lines and the results of MTT assay showed good cytocompatibility in the tested range of concentrations. The growth of Gram‐positive bacteria was inhibited more than Gram‐negative bacteria in the presence of mushroom chitosan extracts, in particular by the chemical one, indicating their efficiency as antimicrobial agents. All these results strengthen the evidence of mushroom polysaccharide preparations availability for biomedical applications. Abstract :